Electrolyte additive composition, electrolyte containing electrolyte additive composition, and preparation method and application of electrolyte additive composition
By using electrolyte additives composed of aluminum alcohol compound and phosphazene compound in lithium-ion secondary batteries, the problems of electrolyte decomposition and uneven interface at high voltage are solved, and the stable operation and safety of the battery under high voltage are achieved.
Patent Information
- Application Number
- CN202510155292.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-12
AI Technical Summary
Existing lithium-ion secondary batteries have the risk of rapid electrolyte decomposition, lithium dendrites formation, positive electrode material structure degradation and safety accidents under high voltages, and uneven electrode/electrolyte interfaces lead to uneven lithium ion flow transmission.
The electrolyte additive composed of aluminum alcohol compound and phosphazene compound is used to form covalent bonds through nucleophilic substitution reactions, which promotes the formation of a three-dimensional polymer network and is uniformly distributed at the electrode/electrolyte interface, reducing the activation energy of lithium ion transmission and improving the stability of the interface.
At a high voltage of above 4.7V, the battery can operate stably, improve the specific capacity and energy density, enhance the thermal stability and flame retardancy of the electrolyte, and reduce the safety risks of the battery.
Smart Images

Figure CN119833757A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and provides an electrolyte additive composition, an electrolyte containing the electrolyte additive composition, and a preparation method and application thereof. Background Art
[0002] Lithium-ion secondary batteries are widely used in portable electronic devices, power batteries, and large-scale energy storage due to their high energy density, long cycle life, low self-discharge, green environmental protection, and no memory effect. In order to further improve the battery life and safety and alleviate consumers' "battery anxiety", the development of high-energy-density and high-safety lithium-ion secondary batteries is an important issue that needs to be solved urgently.
[0003] Increasing the battery's charge cut-off voltage can increase the battery's specific capacity and operating voltage platform, thereby increasing the battery's energy density. Currently, the charge cut-off voltage of the commonly used positive electrode material LiFePO4 for lithium-ion secondary batteries is 3.65V, while that of LiCoO2, LiNi x Co y Mn 1-x-y O2、LiNi x Co y Al 1-x-y The cut-off voltage of O2 charging is 4.2V, and the electrolyte used is mainly a carbonate solution of lithium hexafluorophosphate (LiPF6). However, due to its low decomposition potential, flammability, and difficulty in forming a uniform and stable electrode / electrolyte interface, it will cause rapid decomposition of the electrolyte at higher voltages, increase the number of interfacial side reactions between the electrode and the electrolyte, accelerate the formation of lithium dendrites and the structural degradation of the positive electrode material, and then cause problems such as battery capacity attenuation and failure, and even serious safety accidents such as battery short circuit and fire. Therefore, it is very important to develop an electrolyte with high voltage stability and non-flammability.
[0004] Electrolyte additives are the main means of electrolyte regulation. The addition of additives can directly regulate the components of the electrolyte, thereby changing the properties of the electrolyte. At the same time, additives can also decompose to form an electrode / electrolyte interface layer containing specific components to improve the stability and ionic conductivity of the interface. However, the components of the electrode / electrolyte interface formed by simple chemical decomposition of additives are often unevenly distributed, resulting in uneven lithium ion flow transmission and electrode internal stress. Uneven lithium ion concentration can cause uneven lithium deposition and the formation of lithium dendrites, which can easily pierce the diaphragm and increase the risk of internal short circuit and thermal runaway of the battery. Under high voltage, due to the deep delithiation of the positive electrode material, the lattice parameters have changed significantly, resulting in large mechanical stress. The uneven stress in the electrode will cause microcracks in the positive electrode material due to stress, increase the adverse side reactions between the positive electrode material and the electrolyte, accelerate the structural degradation and capacity decay of the positive electrode material, and significantly increase the interface impedance. In order to ensure uniform transmission of lithium ion flow and uniform distribution of stress in the electrode under high voltage, so that lithium ion secondary batteries can operate safely and stably under high voltage, new interactive additives are needed to improve the uniformity and stability of the electrode / electrolyte interface.
[0005] Among them, cyclotriphosphazene and its derivatives are a class of organic-inorganic hybrid compounds with nitrogen and phosphorus arranged alternately in the skeleton, which are widely studied as flame retardants. For example, Chinese invention patent CN107302108B discloses a flame retardant epoxy trifluorocyclotriphosphazene, which can significantly improve the flame retardant efficiency under the synergistic effect of four flame retardant elements N, P, F and Si as a flame retardant additive for lithium-ion battery electrolyte. However, the application research of cyclotriphosphazene and its derivatives in lithium-ion battery electrolyte mainly focuses on its flame retardancy, and its influence on battery performance still needs to be further studied.
[0006] Therefore, it is necessary to conduct in-depth research on the application of cyclotriphosphazene and its derivatives as electrolyte additives for lithium-ion batteries, especially electrolyte additives suitable for high voltage systems. Summary of the invention
[0007] The present invention aims at solving the problems in the prior art and provides an electrolyte additive composition, an electrolyte containing the electrolyte additive composition and a preparation method thereof.
[0008] The technical solution of the present invention is as follows:
[0009] The present invention provides an electrolyte additive composition, comprising an aluminum alcohol compound and a phosphazene compound; the phosphazene compound has the following structural formula:
[0010]
[0011] Wherein, R1-R6 are each independently selected from fluorine, alkoxy or phenoxy.
[0012] The mechanism of action of the aluminum alcohol compound and the phosphazene compound is that the nucleophilic reagent attacks the electrophilic center and a nucleophilic substitution reaction occurs, that is, the phosphazene compound containing an electron-rich group acts as a nucleophilic reagent to attack the aluminum atom of the aluminum alcohol compound. Due to the lack of electrons, the aluminum atom can accept electron pairs from other reagents containing lone pairs of electrons, thereby causing the alkoxy group of the aluminum alcohol compound to be replaced by the electron-rich group of the phosphazene compound, and a new covalent bond is formed between the two; or the oxygen of the alkoxy group in the aluminum alcohol compound initiates a nucleophilic attack on the phosphorus atom in the phosphazene compound, thereby forming a new covalent bond. Through the nucleophilic substitution reaction between the two compounds, they are tightly connected through covalent bonds.
[0013] In addition, alcohol aluminum compounds can also act as cross-linking agents to promote the formation of three-dimensional polymer networks, thereby making the inorganic products (such as Li3N, Li3P, etc.) generated by the additives during the cycle uniformly distributed in the solid electrolyte interface (SEI) and cathode electrolyte interface (CEI), thereby reducing the activation energy of lithium ion transmission, ensuring the consistency of lithium ion transmission, and reducing the internal stress inside the electrode. It promotes the uniform deposition of lithium under high voltage and inhibits stress cracking and structural degradation of the positive electrode material under high voltage.
[0014] Preferably, the phosphazene compound is one or more of ethoxy(pentafluoro)cyclotriphosphazene (PEPN), pentafluoro(phenoxy)cyclotriphosphazene (FPPN), hexaphenoxycyclotriphosphazene (HPCTP) and hexafluorocyclotriphosphazene (HFPN).
[0015] Furthermore, the mass ratio of the aluminum alcohol compound to the phosphazene compound is 0.1-2:5-10.
[0016] Furthermore, the structural formula of the aluminum alcohol compound is as follows:
[0017]
[0018] Wherein, R7, R8, and R9 are each independently selected from an alkyl group of 1 to 8 carbon atoms.
[0019] Preferably, the aluminum alkoxide compound is selected from one or more of aluminum triethoxide, aluminum isopropoxide, aluminum n-propoxide, aluminum sec-butoxide and aluminum isopentanoxide.
[0020] The present invention also provides an electrolyte comprising an electrolyte solute, a non-aqueous solvent and the electrolyte additive composition according to any one of claims 1-5.
[0021] Furthermore, the electrolyte additive composition is used in an amount of 0.1-20% of the total mass of the electrolyte.
[0022] Preferably, the electrolyte additive composition is used in an amount of 5-15% of the total mass of the electrolyte.
[0023] Furthermore, the amount of the aluminum alcohol compound is 0.1-2% of the total mass of the electrolyte; and / or the amount of the phosphazene compound is 5-10% of the total mass of the electrolyte.
[0024] Preferably, the amount of the aluminum alcohol compound is 0.1-0.5% of the total mass of the electrolyte; and / or the amount of the phosphazene compound is 8-10% of the total mass of the electrolyte.
[0025] More preferably, the amount of the aluminum alcohol compound is 0.5% of the total mass of the electrolyte; and / or the amount of the phosphazene compound is 10% of the total mass of the electrolyte.
[0026] Furthermore, the electrolyte solute is selected from one or more of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB, LiClO4, LiPOF2, and LiBF4.
[0027] Further, the non-aqueous solvent is selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).
[0028] The present invention also provides a method for preparing an electrolyte, which specifically comprises: dissolving an electrolyte solute, an alcohol aluminum compound and a phosphazene compound in a non-aqueous solvent to obtain the electrolyte.
[0029] The present invention also provides the use of the electrolyte composition additive, the electrolyte or the electrolyte prepared by the preparation method in the preparation of lithium ion secondary batteries.
[0030] The present invention also provides a lithium ion secondary battery, which is prepared from a positive electrode material, a negative electrode material and the above electrolyte.
[0031] Furthermore, the positive electrode material is selected from lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2), lithium iron phosphate (LiFePO4), lithium nickel cobalt aluminum oxide (LiNixCoyAl 1-x-y O2), lithium cobalt oxide (LiCoO2), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) and lithium-rich manganese (Li 1+x [NiMnCo] 1-x O2) or more.
[0032] Furthermore, the negative electrode material is selected from any one of graphite, lithium metal, silicon carbon and silicon.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The lithium secondary battery prepared using the electrolyte containing the additive of the present invention can stably operate at a high voltage of more than 4.7V, which is far higher than the charging cut-off voltage of 4.2V under the prior art, greatly improving the specific capacity and energy density of the battery.
[0035] (2) The phosphorus atoms and nitrogen atoms of the phosphazene compound in the composite additive of the present invention have high electronegativity and can attract the surrounding electron cloud to form stable chemical bonds, thereby enhancing the thermal stability of the electrolyte and the SEI and CEI layers; at the same time, they can form new free radicals (such as RPO·) by breaking their own structures, thereby removing combustion free radicals (such as H·, HO·), etc., and interrupting the combustion chain reaction; at the same time, adding an alcohol aluminum compound on the basis of a specific phosphazene compound can further improve its flame retardancy and improve battery performance; the electrolyte containing the composite additive has good thermal stability and flame retardancy, cannot be ignited by open flames, and greatly improves the safety of the battery.
[0036] (3) In addition, the additive composed of the alcohol aluminum compound and the phosphazene compound of the present invention can remove trace water in the electrolyte, inhibit the hydrolysis of electrolyte solutes such as LiPF6, thereby reducing the generation of HF, reducing the corrosion of HF to electrode materials, current collectors, etc., and reducing the generation of gas during the cycle. This is because the phosphazene can provide an electrophilic center to attract the alkoxy group of the alcohol aluminum to initiate a nucleophilic attack, promote the hydrolysis reaction of the alcohol aluminum, consume the trace water in the electrolyte, inhibit the hydrolysis of LiPF6, and thus reduce the generation of HF and its side effects. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited.
[0038] The alcohol aluminum additive (aluminum triethanolate) used in the comparative example of the present invention is prepared according to the method disclosed in "Transformation of bulk alloys to oxide nanowires" (Lei, D. et al. Science. 355: 267-271 (2017)), and the specific preparation process is as follows:
[0039] (1) First, lithium powder and aluminum powder are used as materials for synthesizing LiAl alloy. 0.085g lithium powder and 0.3g aluminum powder (atomic ratio Li:Al=1:1, excess 10% Li) are added to a graphite crucible lined with graphite paper, heated at 800°C for 30 minutes, and then the graphite crucible is taken out of the muffle furnace and the graphite plunger is immediately pressed down to obtain LiAl alloy;
[0040] (2) 0.115 g of LiAl alloy was placed in 20 mL of anhydrous ethanol and placed at 60° C. for 30 h to obtain uniform triethanol aluminum (in the form of nanowires with a diameter of 20-200 nm) through a chemical desalting process.
[0041] Preparation of positive electrode sheet: positive electrode active material LiN i0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are added to N-methyl-2-pyrrolidone (NMP) in a mass ratio of 94:3:3, and stirred evenly to form a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after baking, rolling, and cutting.
[0042] The negative electrode was purchased from Tianjin Zhongneng Lithium Industry Co., Ltd.
[0043] The negative electrode shell, positive electrode shell, stainless steel sheet, gasket and spring were purchased from Dongguan Kelude Experimental Equipment Technology Co., Ltd., model CR2032.
[0044] The diaphragm was purchased from Dongguan Kelude Experimental Equipment Technology Co., Ltd., model number is Celgard 2500.
[0045] Example 1
[0046] Preparation of electrolyte: Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1 as the electrolyte solvent; LiPF6 is added to a concentration of 1M and mixed evenly; 0.5% aluminum triethanolate and 10% ethoxy (pentafluoro) cyclotriphosphazene (PFPN) are added to the electrolyte by mass percentage and mixed evenly.
[0047] Example 2
[0048] The only difference from Example 1 is that the electrolyte additives include 0.5% by weight of aluminum triethoxide and 10% by weight of pentafluoro(phenoxy)cyclotriphosphazene (FPPN).
[0049] Example 3
[0050] The only difference from Example 1 is that the electrolyte additives include 0.5% by weight of aluminum triethoxide and 10% by weight of hexaphenoxycyclotriphosphazene (HPCTP) in the electrolyte.
[0051] Example 4
[0052] The only difference from Example 1 is that the electrolyte additives include 0.5% by weight of aluminum triethoxide and 10% by weight of hexafluorocyclotriphosphazene (HFPN) in the electrolyte.
[0053] Example 5
[0054] The only difference from Example 1 is that the electrolyte additives include 0.5% aluminum isopropoxide and 10% ethoxy (pentafluoro) cyclotriphosphazene (PFPN) by weight of the electrolyte.
[0055] Example 6
[0056] The only difference from Example 1 is that the electrolyte additives use 0.1% aluminum triethoxide and 5% ethoxy (pentafluoro) cyclotriphosphazene (PFPN) in the electrolyte by weight percentage.
[0057] Example 7
[0058] The only difference from Example 1 is that the electrolyte additives use 2% of aluminum triethoxide and 10% of ethoxy (pentafluoro) cyclotriphosphazene (PFPN) by weight of the electrolyte.
[0059] Comparative Example 1
[0060] The only difference from Example 1 is that no electrolyte additive is added.
[0061] Comparative Example 2
[0062] The only difference from Example 1 is that the electrolyte additive uses aluminum triethoxide at a mass percentage of 0.5% of the electrolyte.
[0063] Comparative Example 3
[0064] The only difference from Example 1 is that ethoxy (pentafluoro) cyclotriphosphazene (PFPN) is used as an electrolyte additive at a weight percentage of 10% of the electrolyte.
[0065] Comparative Example 4
[0066] The only difference from Example 1 is that the electrolyte additive uses aluminum triethanolate with a mass percentage of 10.5% of the electrolyte.
[0067] Comparative Example 5
[0068] The only difference from Example 1 is that ethoxy (pentafluoro) cyclotriphosphazene (PFPN) with a mass percentage of 10.5% of the electrolyte is used as the electrolyte additive.
[0069] Comparative Example 6
[0070] The only difference from Example 1 is that the electrolyte additives include 0.5% aluminum triethoxide and 10% hexachlorocyclotriphosphazene (HCPN) in terms of the mass percentage of the electrolyte.
[0071] Test Case
[0072] Assembly and testing of full-cell Li||NCM811: Assemble button cells in the order of negative electrode shell, negative electrode plate, 15μL electrolyte, diaphragm, 15μL electrolyte, positive electrode plate, gasket, shrapnel, and positive electrode shell. At 30°C, let the battery stand for 8 hours, then charge to 4.7V (or 4.2V) at a current of 0.2C, and discharge to 3.0V at a current of 0.5C to obtain the discharge capacity of the battery at 0.5C; cycle the battery 50 times under the above conditions to obtain the discharge capacity of the battery at the 50th cycle, and calculate the capacity retention rate, which is the discharge capacity of the 50th cycle / the discharge capacity of the first cycle.
[0073] Assembly of Li||SS battery and electrolyte electrochemical window test: button cell was assembled in the order of negative electrode shell, lithium sheet, 30μL electrolyte, diaphragm, 30μL electrolyte, stainless steel sheet, gasket, shrapnel, positive electrode shell. The battery was left to stand for 8 hours at 30°C, and then the linear sweep voltammetry (LSV) was used to scan from open circuit voltage to 6V at a scan rate of 1mV / s to obtain the current-potential curve. The potential corresponding to the point where the slope of the curve changed significantly was taken as the decomposition potential of the electrolyte, and the electrochemical window of the electrolyte was determined.
[0074] Electrolyte flame retardancy test: Take 1g of electrolyte in the battery case, use an ignition device to ignite the electrolyte for 5s, then remove the ignition device, and record the time from the removal of the ignition device to the automatic extinguishing of the flame. The extinguishing time corresponding to the unit mass of electrolyte is the electrolyte self-extinguishing time (SET).
[0075] The test results of high voltage full battery cycle performance, electrochemical window and flame retardancy of different electrolytes in the above embodiments are shown in Table 1.
[0076] Table 1 High voltage full battery performance test results
[0077]
[0078] From the results in Table 1, it can be seen that when no electrolyte additive is used, the capacity of the battery decays rapidly at a high charge cut-off voltage, and the electrolyte will continue to burn after being ignited until all the electrolyte is consumed. When only alcohol aluminum compounds are added to the electrolyte, the high voltage cycle stability of the battery is improved to a certain extent, but the flame retardancy of the electrolyte is not improved, and it will continue to burn after being ignited. When only phosphazene compounds are added, the flame retardancy of the electrolyte is improved, and it will not continue to burn. The high voltage cycle stability of the battery is improved to a certain extent, but the capacity decay is still fast. By adding an alcohol aluminum compound and a specific phosphazene compound to the electrolyte at the same time, the electrochemical window of the electrolyte is expanded to varying degrees, and the cycle stability of the battery at a high charge cut-off voltage of 4.7V is significantly improved compared with the comparative examples without using additives and using a single additive, and the specific capacity is also increased by 29.1% compared with 4.2V, and the flame retardant performance is further improved; in addition, when hexachlorocyclotriphosphazene (HCPN) is used in comparative example 4, only one cycle can be achieved; this indicates that the alcohol aluminum compound only has a synergistic effect with the specific phosphazene compound, which effectively improves the high voltage stability of the electrolyte; at the same time, the flame retardant performance of the electrolyte is also significantly improved, and it will not be ignited, which will greatly improve the safety of the battery.
[0079] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. An electrolyte additive composition, characterized in that: It includes an aluminum alcohol compound and a phosphazene compound; the phosphazene compound has the following structural formula: Wherein, R1-R6 are each independently selected from fluorine, alkoxy or phenoxy.
2. The electrolyte additive composition according to claim 1, characterized in that: The phosphazene compound is one or more of ethoxy (pentafluoro) cyclotriphosphazene, pentafluoro (phenoxy) cyclotriphosphazene, hexaphenoxy cyclotriphosphazene and hexafluoro cyclotriphosphazene.
3. The electrolyte additive composition according to claim 1, characterized in that: The mass ratio of the aluminum alcohol compound to the phosphazene compound is 0.1-2:5-10.
4. The electrolyte additive composition according to claim 1, characterized in that: The structural formula of the aluminum alcohol compound is as follows: Wherein, R7, R8, and R9 are each independently selected from an alkyl group of 1 to 8 carbons; The aluminum alcoholate compound is specifically selected from one or more of aluminum triethoxide, aluminum isopropoxide, aluminum n-propoxide, aluminum sec-butoxide and aluminum isopentanol.
5. An electrolyte, characterized in that: The invention comprises an electrolyte solute, a non-aqueous solvent and the electrolyte additive composition according to any one of claims 1 to 4.
6. The electrolyte according to claim 5, characterized in that The electrolyte additive composition is used in an amount of 0.1-20% of the total mass of the electrolyte, preferably 5-15% of the total mass of the electrolyte; The amount of the aluminum alcohol compound is 0.1-2% of the total mass of the electrolyte, preferably 0.1-0.5%; more preferably 0.5%; And / or the amount of the phosphazene compound is 5-10% of the total mass of the electrolyte; preferably 8-10%; more preferably 10%.
7. The electrolyte according to claim 5 or 6, characterized in that The electrolyte solute is selected from one or more of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB, LiClO4, LiPOF2, and LiBF4; the non-aqueous solvent is selected from one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.
8. The method for preparing an electrolyte according to any one of claims 5 to 7, characterized in that: The electrolyte solute, the alcohol aluminum compound and the phosphazene compound are dissolved in a non-aqueous solvent to obtain the electrolyte.
9. Use of an electrolyte composition additive or electrolyte in the preparation of a lithium ion secondary battery, characterized in that: The electrolyte additive composition according to any one of claims 1 to 4, the electrolyte according to any one of claims 5 to 7, or the electrolyte prepared by the preparation method according to claim 8.
10. A lithium ion secondary battery, characterized in that: Prepared from a positive electrode material, a negative electrode material and an electrolyte, wherein the electrolyte is the electrolyte described in any one of claims 5 to 7 or the electrolyte prepared by the preparation method described in claim 8; The positive electrode material is selected from any one of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium nickel manganese oxide and lithium-rich manganese oxide; The negative electrode material is selected from any one of graphite, lithium metal, silicon carbon and silicon.
Citation Information
Patent Citations
A flame retardant, a siloxyfluorocyclic triphosphazene, and its synthesis method.
CN107302108B
Long life lithium batteries with stabilized electrodes
CN101894975A
High voltage lithium-ion battery electrolyte and lithium-ion battery
CN103633369A
Electrolyte for improving cycling stability of lithium titanate battery, and preparation method of electrolyte
CN107394270A
Electrolyte for nonaqueous battery, and the nonaqueous battery
JP1999176468A
Cited By
Electrolyte, preparation method thereof and lithium ion battery
CN121642145A
Electrolyte additive composition, electrolyte, preparation method and application of electrolyte and lithium ion secondary battery
CN121905966A
Composite electrolyte additive composition, electrolyte, preparation and application
CN122091751A